Dialogue in print advertising messages - Kazlauskaitė, Rūta (Lietuvių kalba, 2015)
The interrelations between the participants of the act of communication are based on a dialogue. Print advertising messages are the way of addressing potential customers (addressee). Advertisers (addresser) aim to induce consumers’ desire to have a suggested product or service, to obtain it. To make advertising effective the conversation between close people is imitated, means of expression characteristic to colloquial speech and usual for everyone are used. The article deals with the forms and peculiarities of the dialogue that is actualized in print advertising messages. The statements of one speaker (usually it is the addresser), i. e. cues, can be unexpressed, unspoken, but they are crucial, because they condition the content and form of the expressed (second collocutor’s) speech – in this case a dialogical monologue is used. The participant of the dialogue – the addresser – speaks on his/her behalf or indirectly through the characters of the advertisements. In advertising messages three types of dialogue are actualized: 1. imitated dialogue between an addresser and an addressee – it is composed of questions and answers; 2. direct address of the speaker (addresser) expressed in a monologue; 3. hidden address of the speaker (addresser) expressed in the speech of the characters of the advertisement: monologues and dialogues. Dialogues show that those who suggest the product present themselves as solvers of everyday life problems, order makers, providers and promoters of welfare and satisfaction. They are helpful and kind people caring for the consumers of the product and close to them in various nice features. The main means of expression of the dialogue – addresses and forms of imperative mood (by which the straightforward urge to buy is expressed) or the forms of the pronouns tu, jūs, mes (you singular, you plural, we) and the present tense (by which the advertiser’s intentions are concealed).